Analysis of the Transition Time From Air to Oxy-Combustion - Lasek Janusz; Lajnert Radosław; Głód Krzysztof; Zuwała Jarosław (Chemical and Process Engineering)
In this paper some issues of the transition process from air- to oxy-combustion were investigated. Advantages of flexible combustion were described. Flexible combustion tests carried out at four European plants and five plants outside Europe of different scales of process and test parameters were presented. An analysis of the transition time from air to oxy-combustion of different laboratory and pilot scale processes was carried out. The “first-order + dead time” approach was used as a model to describe transition process. Transitional periods between combustion modes and characteristic parameters of the process were determined. The transition time depends not only on the facility’s capacity but also it is impacted by specific operational parameters.